Diagnosis of Fire Simple R.C Building Members Damages By Using Expert System - M. Sagheer, Ali; A. Mansour Al-Kubaisy, Yousif; Z. Hussein Al-Qaissi, Haitham (Iraqi Journal of Civil Engineering, 2008)
During the last four decades, incidence of failure of reinforced concrete structures has been seen widely for many reasons, such as increasing service loads ,war accidents, fire and/or durability problems and the economic losses due to such failures are costly. Nowadays, the size and the form of repair and rehabilitation market are too large since there has been an increased emphasis on repair and retrofitting of defected structures over demolition and new construction. An expert system is an interactive computer-based decision tool that uses both facts and heuristics to solve difficult decision problems based on knowledge acquired from an expert. To realize these requirements, a logic programming Prolog language was utilized together with diagnosis technology. The logic programming language formalizes the domain knowledge. The expert system Diagnosis of Fire Simple R.C Building Members Damages (DFSRCMD) developed in this paper is a diagnostic advisory system, which can be used as an alternative to the human expert, to give technical decisions in diagnosing fire damages in R.C. structural elements: beams, columns and slabs.